Mekanisme Good Corporate Governance Terhadap Nilai Perusahaan: Efek Moderasi Profitabilitas - Meyliana, Santika; Machmuddah, Zaky; Utomo, St. Dwiarso (Universitas Dian Nuswantoro, 2024)
This study aims to explore the impact of Good Corporate Governance (GCG) mechanisms involving the audit committee, independent board of commissioners, and institutional ownership on firm value proxied by PBV with profitability proxied by ROA as a moderating variable. This research focuses on property and real estate sector companies during 2020-2022 and sampling was carried out using purposive sampling method resulting in sample data of 99 entities. Data analysis uses the PLS-SEM approach with the WarpPLS 7.0 analysis tool. The final results showed the influence of the audit committee, institutional ownership, and independent board of commissioners on firm value. In addition, profitability is able to strengthen the impact of the audit committee on firm value, but profitability does not have an impact on the influence of the independent board of commissioners and institutional ownership on firm value.